Effect of education and telephone counseling on adherence to treatment and challenges experienced in anti-TNF-α treatment: a pilot study. Issue 1 (2nd January 2018) - Ozkaraman, Ayse; Alparslan, Guler Balcı; Babadağ, Burcu; Kaşifoğlu, Timucin; Baydemir, Canan
Abstract : Background: Anti-tumor necrosis factor-α (anti-TNF-α) drugs used in the treatment of rheumatologic diseases. Objective: This study was conducted to examine the effects of education about the drug use and consultation by telephone calls on treatment adherence and drug-induced challenges in patients under 'the first anti-TNF-α treatment'. Methods: The research instruments were used Morisky's Questions-Self Report Measure of Adherence, drug-induced problems determination form. Results: In the Morisky Drug Adherence Scale, the answers to the questions 'Do you forget to use your drugs?' and 'Are you sometimes careless when you use your drug?' changed from 'yes' to 'no', and the difference was statistically significant ( p  < .001, p  < .001). 21.9% of the intervention group and 34.4% of the control patients reported they experienced some problems ( χ 2  = 3.244, p  = .087). Conclusion: Education is effective on adherence to drug treatment in patients on anti-TNF-α treatment however telephone counselling had no effect on challenges experienced.